2017
DOI: 10.1038/srep42548
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid-β Oligomers Interact with Neurexin and Diminish Neurexin-mediated Excitatory Presynaptic Organization

Abstract: Alzheimer’s disease (AD) is characterized by excessive production and deposition of amyloid-beta (Aβ) proteins as well as synapse dysfunction and loss. While soluble Aβ oligomers (AβOs) have deleterious effects on synapse function and reduce synapse number, the underlying molecular mechanisms are not well understood. Here we screened synaptic organizer proteins for cell-surface interaction with AβOs and identified a novel interaction between neurexins (NRXs) and AβOs. AβOs bind to NRXs via the N-terminal histi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
94
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(100 citation statements)
references
References 61 publications
6
94
0
Order By: Relevance
“…IgSF21 deletion constructs were generated by inverse PCR using mouse IgSF21-HA as the template to delete the regions encoding aa 31–141 (IgSF21ΔIg1) or aa 348–431 (IgSF21ΔIg2). A series of extracellularly HA-tagged neurexin (HA-NRX) constructs, HA-CD4 and HA-NLG2 were previously described 29 , 56 . For the pDisplay-NRX2α constructs, the following coding regions of NRX2αS1–S4(+) were subcloned into pDisplay (Invitrogen): aa 29-199 (LNS1), aa 29-309 (LNS1-EGF1), aa 29-499 (LNS1-LNS2) and aa 29-680 (LNS1-LNS3).…”
Section: Methodsmentioning
confidence: 99%
“…IgSF21 deletion constructs were generated by inverse PCR using mouse IgSF21-HA as the template to delete the regions encoding aa 31–141 (IgSF21ΔIg1) or aa 348–431 (IgSF21ΔIg2). A series of extracellularly HA-tagged neurexin (HA-NRX) constructs, HA-CD4 and HA-NLG2 were previously described 29 , 56 . For the pDisplay-NRX2α constructs, the following coding regions of NRX2αS1–S4(+) were subcloned into pDisplay (Invitrogen): aa 29-199 (LNS1), aa 29-309 (LNS1-EGF1), aa 29-499 (LNS1-LNS2) and aa 29-680 (LNS1-LNS3).…”
Section: Methodsmentioning
confidence: 99%
“…At the synapse level, NLGN1 and NLGN2 are mostly localized at excitatory and inhibitory synapses, respectively, whereas NLGN3 is localized at both excitatory and inhibitory synapses (Song et al, 1999 ; Varoqueaux et al, 2004 ; Budreck and Scheiffele, 2007 ). Artificial synapse formation assays have shown that NLGNs have a synaptogenic activity to induce presynaptic organization of excitatory and inhibitory synapses (Scheiffele et al, 2000 ; Graf et al, 2004 ; Chubykin et al, 2005 ; Craig et al, 2006 ; Naito et al, 2017b ) through their trans-interaction with presynaptic NRXs (Ko et al, 2009b ; Gokce and Südhof, 2013 ). Further, a recent study using NLGN1-4 conditional KO mouse brain slices with rescue experiments has shown that the NLGN1 extracellular domain, particularly its trans-interaction with presynaptic NRXs, is crucial for LTP (Wu et al, 2019 ).…”
Section: Neurexin-based Synaptic Organizing Complexesmentioning
confidence: 99%
“…LRRTM3/4 are highly expressed in the hippocampal DG, the cerebral cortex layer 2 and moderately expressed in the cerebral cortex layers 3–6 (Laurén et al, 2003 ). LRRTMs can promote the presynaptic organization of excitatory, but not inhibitory, synapses (Ko et al, 2009a ; Linhoff et al, 2009 ; de Wit et al, 2013 ; Naito et al, 2017b ). Interestingly, LRRTM1/2 bind to SS4-negative NRX [NRX SS4(−)], but not SS4-positive NRX [NRX SS4(+)], regardless of α- and β-NRX isoforms (Ko et al, 2009a ; Siddiqui et al, 2010 ).…”
Section: Neurexin-based Synaptic Organizing Complexesmentioning
confidence: 99%
See 2 more Smart Citations